2016
DOI: 10.4081/ejtm.2016.5958
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity counteracts tumor cell growth in colon carcinoma C26-injected muscles: an interim report

Abstract: Skeletal muscle tissue is a rare site of tumor metastasis but is the main target of the degenerative processes occurring in cancer-associated cachexia syndrome. Beneficial effects of physical activity in counteracting cancer-related muscle wasting have been described in the last decades. Recently it has been shown that, in tumor xeno-transplanted mouse models, physical activity is able to directly affect tumor growth by modulating inflammatory responses in the tumor mass microenvironment. Here, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In addition, our observations on muscle denervation in cachexia could explain a previously reported subclinical myopathy in cancer patients, characterized by central nuclei in myofibers [24]. Since muscle regeneration is strongly inhibited in cachexia [20,[57][58][59], the central nuclei in cachectic muscles were so far unaccounted for, while our proposed model based on denervation could provide and explanation for this phenomenon (graphical abstract).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, our observations on muscle denervation in cachexia could explain a previously reported subclinical myopathy in cancer patients, characterized by central nuclei in myofibers [24]. Since muscle regeneration is strongly inhibited in cachexia [20,[57][58][59], the central nuclei in cachectic muscles were so far unaccounted for, while our proposed model based on denervation could provide and explanation for this phenomenon (graphical abstract).…”
Section: Discussionmentioning
confidence: 60%
“…There are published studies that show significant decrease in muscle mass in early and late stages of cancer progression that ultimately leads to a decrease in muscle function [ 47 – 50 ]. It has been observed that this process can be mediated through inflammation from presence of a tumor [ 47 , 48 ]. Interestingly, a recent study by Yu et al report that the compound ghrelin was shown to inhibit Dox-induced apoptosis in the gastrocnemius muscle, suggesting a therapeutic role in the associated cancer cachexia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Beside pharmacological treatments, many studies including ours have established that exercise counteracts cachexia and sarcopenia. 32-35 The mechanisms underlying the beneficial effects of exercise against cachexia include autophagic flux regulation, 36 the reduction of Pax7 expression in satellite cells, 37 and the release of Hsp60 from muscle cells. 38 This topic was recently reviewed, 39-41 and it will be not further discussed here.…”
Section: Countermeasures: Would Exercise Be Effective Against Chemothmentioning
confidence: 99%